2012
DOI: 10.1111/j.1751-7893.2012.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style predicts 6‐month improvement in psychoticism in persons with at‐risk mental states for psychosis

Abstract: The three attachment prototypes that predicted improvement in psychoticism (secure, preoccupied and dismissing) share the existence of at least one positive psychological model (either about self or about others). It may be that the psychosocial intervention helped ARMS patients to disconfirm negative models and/or reinforce positive ones. Patients' attachment styles were not related to baseline clinical severity but impacted improvement of positive symptoms. These findings appear consistent with evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“…In one cross-sectional study using the self-report Revised Adult Attachment Scale (Collins, 1996), 80% of CHR young adults showed evidence of insecure attachment (Gajwani et al, 2013). Further, in a prospective study with a sample of 31 ARMS individuals (mean age = 15.7 years), Quijada et al (2012) examined the relationship between baseline attachment, symptoms and social functioning after a 6-month psychosocial intervention. The majority of individuals in this ARMS sample was classified, on the basis of the observer-rated Relationships Questionnaire (Bartholomew and Horowitz, 1991), as fearfully attached (71%), followed by preoccupied (16.1%) and dismissing attachment (6.4%).…”
Section: Trauma Attachment and Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…In one cross-sectional study using the self-report Revised Adult Attachment Scale (Collins, 1996), 80% of CHR young adults showed evidence of insecure attachment (Gajwani et al, 2013). Further, in a prospective study with a sample of 31 ARMS individuals (mean age = 15.7 years), Quijada et al (2012) examined the relationship between baseline attachment, symptoms and social functioning after a 6-month psychosocial intervention. The majority of individuals in this ARMS sample was classified, on the basis of the observer-rated Relationships Questionnaire (Bartholomew and Horowitz, 1991), as fearfully attached (71%), followed by preoccupied (16.1%) and dismissing attachment (6.4%).…”
Section: Trauma Attachment and Psychosismentioning
confidence: 99%
“…Improvement in attenuated positive symptoms at 6 months was associated with baseline secure, preoccupied and dismissing attachment styles. According to Quijada et al (2012), secure, preoccupied and dismissing attachment styles, all share the presence of at least one positive internal working model indicating that psychotherapeutic interventions, at least during the early stages of psychotic illnesses, may benefit from a positive internal working model, either of the self or of others. Further, these data suggest that individuals who hold negative internal models of both self and others in the context of fearful attachment relationships may be at greater risk for a poorer clinical course.…”
Section: Trauma Attachment and Psychosismentioning
confidence: 99%
“…Consistent with findings in schizophrenia, males at CHR of psychosis tend to show poorer premorbid functioning than CHR females (Salokangas et al, 2014; Tarbox et al, 2013). Furthermore, poor premorbid functioning has been shown to be associated with later poorer outcome such as increased disorganization and negative symptom severity (Quijada et al, 2012) and low functional outcome (Salokangas et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have also found that secure attachment predicted better functioning in different types of mental disorders (e.g., Meyer et al, 2001). Similarly, we previously found that secure attachment predicted better functioning after 6 months of treatment in ARMS patients (Quijada et al, 2012). In that study secure attachment also predicted improvement in psychoticism and disorganization, but these associations have not emerged at the one-year follow-up.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study with ARMS patients (Quijada et al, 2012), we found that attachment style predicted symptom improvement after six months of psychosocial treatment. Specifically, a high level of secure attachment predicted improvement in psychoticism, disorganization and functioning, and higher levels of preoccupied and dismissing styles also predicted improvement in psychoticism.…”
Section: Introductionmentioning
confidence: 82%